Measuring expansion from macro‐ to nanoscale using NPC as intrinsic reporter. Issue 8 (28th May 2019) - Pesce, Luca; Cozzolino, Marco; Lanzanò, Luca; Diaspro, Alberto; Bianchini, Paolo
Abstract: Expansion microscopy is a super‐resolution method that allows expanding uniformly biological samples, by increasing the relative distances among fluorescent molecules labeling specific components. One of the main concerns in this approach regards the isotropic behavior at the nanoscale. The present study aims to determine the robustness of such a technique, quantifying the expansion parameters i.e. scale factor, isotropy, uniformity. Our focus is on the nuclear pore complex (NPC), as well‐known nanoscale component endowed of a preserved and symmetrical structure localized on the nuclear envelope. Here, we show that Nup153 is a good reporter to quantitatively address the isotropy of the expansion process. The quantitative analysis carried out on NPCs, at different spatial scales, allows concluding that expansion microscopy can be used at the nanoscale to measure subcellular features with an accuracy from 10 to 5 nm. Therefore, it is an excellent method for structural studies of macromolecular complexes. Abstract : Imaging NUPs at different expansion factors, the images are acquired using STED nanoscopy.